Kinerja Guru SDN Bambu Apus 03 dipengaruhi oleh Insentif melalui Motivasi Kerja sebagai Variabel Mediasi - Muhamad Hafedz Hanawi; Eddy Sanusi Silitonga (Jurnal Manajemen Bisnis Krisnadwipayana, 2026)
This study aims to determine the effect of incentives on teacher performance at SDN Bambu Apus 03 through work motivation. The research method used was quantitative. Data collection techniques were conducted through questionnaires. Using a saturated sampling method. Technique analyzed using path analysis. The results of the study 1) Incentives have a positive and significant effect on teacher performance; 2) Incentives have a have and significant effect on work motivation; 3). Work motivation have a positive and significant effect on teacher performance; 4) Work motivation has been proven to be able to mediate the influence of incentives on teacher performance.